Petrochemical characteristics of ancient weathering crusts with scandium concentrations in the Nakyn kimberlite field - R. U. Eremenko; P. A. Ignatov; P. N. Illarionov (Известия высших учебных заведений: Геология и разведка)
Background. The study examines the petrochemical characteristics of clayey deposits from the Dyakhtar Formation in the Nakyn Kimberlite Field, which contain material from redeposited weathering crusts of the Late Triassic to the Early Jurassic age. Currently, this Formation is considered the most promising for scandium mineralization compared to other areas in the Malo-Botuobinsky and Ygyattinsky diamond-bearing regions of Yakutia with the identified scandium concentrations.   Aim. To establish the geochemical characteristics of scandium concentrations in the sediments of the Dyakhtar formation of the Nakyn kimberlite field.   Materials and methods. Using petrochemical modules, 9022 X-ray fluorescence analyses of rocks of the Dyakhtar formation were analyzed, performed at the Vilyui Geological and Exploration Laboratory of ALROSA,   Results. The recalculation of the petrochemical modules has revealed that the Dyakhtar Formation comprises the following components in different proportions: clayey rocks (42 %), clayey silicites (31 %), weak clayey silicites (15 %), hydrolyzate clayey rocks (9 %) with an admixture of silicites (4 %). The vast majority of samples with scandium concentrations exceeding 100 g/t were found in hydrolyzate clayey rocks (83 %), which contain products of mature weathering crusts. In addition, scandium-bearing rocks are characterized by formation under continental conditions, by normaliron content and lack of translocation, as well as a weak alkaline environment.   Conclusion. The observed systematic changes in the correlation coefficients Sc/V, Sc/Ti, Sc/K, and Sc/Rb with increasing scandium concentrations suggest probable forms of scandium occurrence in vanadium-bearing titanomagnetite and its sorption in montmorillonite.